Study of the scalar-fermionic model containing linear lagrangian fields of matter within the framework of minimal coupling - Tsyba, P.Yu.; Altayeva, G.S.; Razina, O.V. (Karagandy University of the name of acad. E.A. Buketov, 2023)
In this article, we study a model of the universe with the scalar field and the fermionic field interacting via a Yukawa-type potential. In the model, the component contributions of each of the fields are determined to the total density and pressure of dark energy. We have considered the solution of the cosmological model for the scale factor with two functional time dependences. The Yukawa-type field does not give its input to the general pressure. In the power law case, there is a significant contribution to the total increase in pressure, to the exponential — the scalar field. There are many cases when the universe makes a transition between successive epochs in various models of cosmological expansion. These regularities impose some restrictions on the profile of the scalar- fermionic field interaction and the general cosmological dynamics. Energy conditions were found to check the model under the study. In the studied model, the null energy condition, the strong energy condition, the dominant energy condition are fulfilled, and the weak energy condition, which is not mandatory, is not fulfilled. It is shown how it is possible to connect the cosmographic parameters — parameters of deceleration q, jerk j and snap s with the power low the scale factor. We investigated these restrictions using cosmological solutions with an evolving equation of state, such that a smooth transition between different epochs can always occur in the universe. The scalar-fermionic model under study describes the accelerated modes of expansion of the universe. The obtained solutions correspond to the results predicted by the theory and observational data.
Минималды өзара әсерлесуін қамтитын материя өрістерінің сызықты лагранжиандары бар скалярлық-фермиондық модельді зерттеу
Исследование скалярно-фермионной модели, содержащей линейные лагранжианы полей материи, в рамках минимального взаимодействия
Keywords: scalar field; fermionic field; Yukawa-type interaction; minimal coupling; energy condition; the cosmography